Network relations and innovative performance - Vieira, Filipa Dionísio (2009)
Eight firms of the Portuguese moulds industry, all located in the region of Marinha Grande, were analysed as it regards their patterns of relationships with other actors within the sector or outside the sector, and its correlation with innovative performance. The information obtained through intensive observation allowed for the creation of an observation model of the moulds industry. This model is based on the type of existing interactions between firms (customers, suppliers, competitors) and between firms and other institutions (academic institutions, technological centres, research institutions). The firms were not randomly chosen, and it was determinant for their inclusion in the sample their innovative reputation or performance. Although all the sample firms belong to the same industrial industry, different characteristics have emerged, allowing their grouping and classification along the lines of a value chain. Some of the firms are typically and almost exclusively producers, and their project and engineering capacity is very limited. R&D activities and product engineering and design activities are non-existent. A second category of firms have very well developed project and engineering capacities, as well as productive capacity, and are able to develop innovative solutions to demanding costumers. Information sources for innovation are essentially internal, coming out of R&D, and product engineering and design activities, developed internally. There is another category of firms that have no internal production capacity, which is contracted out to other firms. The firms have different innovative behaviours, depending on the partner with whom informal relations are established. In general, the relations between firms and other firms, with firms and customers, with firms and suppliers, and even with firms and their competitors are extremely strong. However relations between firms and academic institutions, technological centres or research institutions are, as a rule, rarer and weaker, but the firms that have more relations with these kind of partners are also the more innovative ones and the more independent of customers. The relations that are established by the firm vary according to the characteristics of the firm, namely its particular abilities which are associated with each nuclear area, their strategic position for the knowledge acquisition (i.e. from external sources) and knowledge creation (i.e. own R&D activities), and the position in the industry value chain. A model was constructed, based on the different relations profiles of the firms, on the position within the value chain that the firm occupies, and on the level of innovative capacity of the firm. The model proves to be very useful in the analysis of the behaviour of the industry, by permitting a categorisation of each firm, and providing a clear picture of the industry as a whole. This research work is important because it permits the systematization and generalisation of the innovative dynamics in this industry.